Gospodarka powierzchnią oraz charakterystyka drzewostanów i siedlisk na rekultywowanych zwałach odpadów górnictwa węgla kamiennego na obszarze nadleśnictwa Rybnik (rejon GOP) = Areal balance management, tree stands and sites characteristic on a reclaimed spoil heap of hard coal mining in the Rybnik forest inspectorate (upper silesian industrial region-GOP) - Pietrzykowski, Marcin; Krzaklewski, Wojciech; Tomanek, Malwina; Hajduk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The surface areas requiring reclamation in Poland amounts 64,000 ha, of which, 44,000 ha are occupied by mining. The predominant reclaimed postmining use is forestery (60%). In the area of Upper Silesia, spoil heaps pose a threat to the environment, and they are often deposited on surfaces excluded from forest production.
Keywords: górnictwo węgla kamiennego; rekultywacja; zwałowisko; bilans powierzchniowy; siedliska leśne; drzewostany; hard coal mining; spoil heap; reclamation; areal balance; stand trees; forest habitats